Method for preparing high-strength engineering plastic from recycled PA66 plastic and application of high-strength engineering plastic

By using recycled PA66 plastic and modified carbon fibers, combined with side feeding and fiber-adding technology, high-strength engineering plastics with excellent mechanical properties were prepared, which solved the problems of poor bonding and insufficient mechanical properties of existing carbon fiber reinforced nylon composite materials, and achieved low carbon environmental protection and green circulation effects.

CN119610452AActive Publication Date: 2025-03-14GUANGDONG BOSHIDA NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411658440.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing carbon fiber reinforced nylon composite materials have problems such as poor bonding between carbon fiber and nylon and insufficient mechanical properties.

Method used

High-strength engineering plastics are prepared by using recycled PA66 plastics and using silane coupling agent and polyvinyl alcohol modified carbon fibers as reinforcement agents, and combined with the fiber addition process of side feeding.

Benefits of technology

The prepared high-strength engineering plastic has excellent bending performance, impact performance and tensile performance, which can meet the use requirements of office seats and other industries, and at the same time achieve good results of low-carbon, environmentally friendly and green circulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a method for preparing high-strength engineering plastic from recycled PA66 plastic and application of the high-strength engineering plastic, and relates to the technical field of chemical engineering. The method at least comprises the following steps: warehousing and homogenizing the recycled PA66 plastic; crushing the homogenized PA66 plastic, uniformly premixing the crushed PA66 plastic with a chain extender and an antioxidant, and performing a first extrusion process to obtain rPA66; putting part of the rPA66, the antioxidant, the lubricant, the compatibilizer, the black sand and the light stabilizer into a high-speed mixer, and uniformly mixing to obtain a premix; and performing a second extrusion process on the premix, the modified carbon fiber and the remaining rPA66 to obtain the high-strength engineering plastic prepared from the recycled PA66 plastic, wherein the modified carbon fiber is obtained by modifying a silane coupling agent, carbon nanotubes and polyvinyl alcohol. The high-strength engineering plastic with excellent mechanical properties is obtained by modifying the carbon fibers through the grafted silanized carbon nanotubes and the polyvinyl alcohol to serve as a reinforcing agent for recycling the PA66 and cooperating with an optimized side feeding and fiber adding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical engineering, and in particular to a method for preparing high-strength engineering plastics by utilizing recycled PA66 plastics and application thereof. Background Art

[0002] With the increasing progress and development of society, people have higher and higher requirements for the lightweight and high-performance quality of office chairs and gaming chairs. Components in industries such as automobiles, electronics and mechanical equipment are developing towards lightweight and miniaturization. More and more metal materials are gradually being replaced by polymer composite materials. At the same time, the policies of "replacing steel with plastic" and plastic recycling are constantly being promoted. The development of other thermoplastic composite materials with high strength, high modulus, light specific gravity, wear resistance and corrosion resistance, excellent surface and good heat resistance has become a hot spot for new product development in the market.

[0003] Polyamide resin (PA), commonly known as nylon, is an important thermoplastic engineering plastic. It is widely used in automobiles, mechanical parts, electronics, home appliances and other fields due to its many excellent properties such as high strength, good self-lubrication, wear resistance, oil resistance and easy molding and processing. However, due to the presence of hydrogen bonds, nylon 66 molecules have strong water absorption, resulting in poor product dimensional stability, poor resistance to strong acids and alkalis, and low dry and low-temperature impact strength, which limits its application. Therefore, nylon 66 needs to be modified by reinforcement, filling, toughening, flame retardancy and other modifications to meet different usage requirements.

[0004] Carbon fiber reinforced nylon composite materials not only maintain the inherent advantages of nylon resin such as chemical resistance, corrosion resistance, and good processability, but also have greatly improved mechanical properties, heat resistance, and dimensional stability. Excellent performance makes carbon fiber reinforced nylon composite materials more and more valued, and are also widely used in cutting-edge fields such as aerospace and civil fields such as automotive chemicals. However, carbon fiber has fewer functional groups on the surface of carbon fiber, is inert on the surface, and has poor bonding with nylon 66. Therefore, how to use recycled PA66 plastics to prepare high-strength engineering plastics has become a problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing high-strength engineering plastics by recycling PA66 plastics and its application, so as to solve the following technical problems: Existing carbon fiber reinforced nylon composite materials have the problems of poor bonding between carbon fiber and nylon and poor mechanical properties of the composite materials.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing high-strength engineering plastics by using recycled PA66 plastics, comprising at least the following steps: The recycled PA66 plastic is put into the warehouse for homogenization; The homogenized PA66 plastic is crushed, premixed evenly with the chain extender and the first antioxidant, and subjected to a first extrusion process to obtain rPA66; Put part of the rPA66, the second antioxidant, the lubricant, the compatibilizer, the black sand and the light stabilizer into a high-speed mixer and mix them to obtain a premix; The premix, the modified carbon fiber and the remaining rPA66 are subjected to a second extrusion process to obtain a high-strength engineering plastic prepared by using recycled PA66 plastic; Wherein, the modified carbon fiber is obtained by modification with silane coupling agent, carbon nanotubes and polyvinyl alcohol.

[0007] Preferably, the prepared high-strength engineering plastic comprises at least the following raw materials in parts by weight: rPA66 45.0-50.0; Modified carbon fiber 22.0-29.0; Grafting extender 3.5-6.0; Lubricant 0.2-0.4; Second antioxidant 0.1-0.2; Black sand 0.08-0.1; Light stabilizer 0.2-0.4.

[0008] Preferably, the method for preparing the modified carbon fiber comprises at least the following steps: The carbon fiber is condensed and refluxed in acetone at 60-80°C for 20-26 hours, rinsed and soaked with deionized water, and dried in a blast oven at 80-90°C for 10-15 hours to obtain desizing carbon fiber; The desized carbon fiber is immersed in a 1-3 wt % Michaelis acid ethanol solution at 20-30° C. for 2-4 hours, then rinsed to remove insoluble impurities on the surface, and dried in a blast oven at 80-90° C. for 10-15 hours to obtain an activated carbon fiber; Dispersing carbon nanotubes in a silane coupling agent solution, magnetically stirring for 20-40 minutes, preparing a carbon nanotube suspension system with a mass fraction of 0.4-0.6%, soaking the activated carbon fiber in the carbon nanotube suspension system for 5-20 minutes, taking it out, and then putting it in a blast oven at 80-90° C. to dry for 3-5 hours, using a 1:1 mixed solution of deionized water and ethanol for ultrasonic cleaning, and after cleaning, putting it in a blast oven at 80-90° C. to dry for 3-5 hours to obtain carbon fiber grafted with silanized carbon nanotubes; Polyvinyl alcohol is dissolved in dichloromethane to prepare a polyvinyl alcohol-dichloromethane solution with a concentration of 0.3-0.6%, and the carbon fiber grafted with silanized carbon nanotubes is immersed in the polyvinyl alcohol-dichloromethane solution for 5-30 minutes, drained, and dried in a forced air oven at 80-90° C. for 3-5 hours to obtain the modified carbon fiber.

[0009] Preferably, the first extrusion process and the second extrusion process are both carried out in a co-rotating twin-screw extruder, the premix is ​​fed into the first side feeding port of the co-rotating twin-screw extruder, the modified carbon fiber is fed into the second side feeding port of the co-rotating twin-screw extruder, and the remaining rPA66 is fed into the main feeding port of the co-rotating twin-screw extruder.

[0010] Preferably, the chain extender is a diepoxy group chain extender epoxy resin, and the first antioxidant is antioxidant 1010.

[0011] Preferably, the second antioxidant is any one or more of a hindered phenol antioxidant or a phosphite antioxidant, the lubricant is CF-201, the compatibilizer is a maleic anhydride grafted polyolefin elastomer or a maleic anhydride grafted epoxy resin, the black sand is carbon black or a coupling agent, the light stabilizer is any one or more of a hindered phenol stabilizer, a phosphite stabilizer, a cuprous halide composite stabilizer or a stabilizer containing a dibenzene functional group compound, the carbon fiber is a carbon fiber filament, and the size of the carbon fiber filament is 5-15 mm.

[0012] Preferably, the rotation speed of the first extrusion process is 300-500 rpm and the temperature is 240-270°C.

[0013] Preferably, the rotation speed of the second extrusion process is 300-500 rpm and the temperature is 240-270°C.

[0014] Preferably, the recycled PA66 plastic, before being put into storage for homogenization, is at least unpacked, roughly sorted to remove large impurities, remove magnetic metals, non-magnetic metals, manually sorted, wet crushed, washed with hot alkaline water to remove oil, dried, electrostatically sorted, and infrared and color fine sorted.

[0015] A method for recycling PA66 plastic to prepare high-strength engineering plastics as described in any of the above items, and the application of the high-strength engineering plastics in office chairs, gaming chairs, home appliances, automobiles or power tool industries.

[0016] Beneficial effects of the present invention: The present application utilizes recycled PA66 plastic to prepare high-strength engineering plastics, uses carbon fiber modified with silane coupling agent and polyvinyl alcohol as a reinforcing agent for recycled PA66, and cooperates with a side-feeding fiber adding process to prepare high-strength engineering plastics. The prepared high-strength engineering plastics have excellent bending properties, impact properties and tensile properties, and can meet the use requirements of office chairs or e-sports chairs. The high-strength engineering plastics of the present application achieve low-carbon, environmental protection, and green recycling effects, have a simple process, and have certain cost advantages, and are suitable for industrial mass use.

[0017] This application utilizes silanized carbon nanotubes and silane coupling agents to be grafted onto carbon fibers. Silanized carbon nanotubes are evenly grafted onto the surface of carbon fibers. The carbon nanotubes grafted with silane coupling agents have cross-linked network particles formed by silane, which improves the interfacial bonding between carbon fibers and PA66. On the one hand, the interfacial bonding between carbon fibers and PA66 can be enhanced by using carbon nanotubes grafted with silane coupling agents to form covalent bonds with carbon fibers; on the other hand, the silane coupling agent will form a layer of cross-linked mesh structure on the surface of carbon fibers to improve the wettability of fibers and PPA66. Carbon fibers with epoxy groups have good interfacial bonding with the PA66 matrix. When the composite material is subjected to stress, the PA66 matrix can transfer stress to the carbon fiber skeleton through the interface, thereby enhancing the mechanical properties of the composite material. At the same time, carbon fibers have good stiffness. When the composite material is subjected to stress, within a certain range, the bending properties of the composite material are enhanced as the content of carbon fibers increases.

[0018] The present application uses a polyvinyl alcohol solution to cover a layer of polyvinyl alcohol film on the carbon fiber and carbon nanotubes. The role of polyvinyl alcohol and carbon fiber is physical adhesion, mainly relying on intermolecular forces and physical bites. The covered polyvinyl alcohol film further improves the adhesion of the modified carbon fiber and the compatibility of the modified carbon fiber with PA66, thereby improving the reinforcing effect of the modified carbon fiber on PA66. The present application also uses Michaelis acid to activate the carbon fiber before modification, which can better introduce polar oxygen-containing functional groups on the surface of the carbon fiber, so that the oxygen-carbon ratio of the carbon fiber surface increases, the surface roughness of the carbon fiber increases, and the surface energy of the carbon fiber is greatly improved, further improving the reinforcing effect of the carbon fiber.

[0019] In the present application, carbon fiber is carbon fiber filament, and the carbon fiber raw material with longer length is selected, which is conducive to improving the performance of composite materials. Under the main feeding fiber adding process, the carbon fiber processing history is longer, the shearing effect of the screw is stronger, the fiber length is shorter, and the material mechanical properties are poor. And in the present application, the premix is ​​fed into the first side feeding port of the co-rotating twin-screw extruder, the modified carbon fiber is fed into the second side feeding port of the co-rotating twin-screw extruder, and the remaining part of rPA66 is fed into the main feeding port of the co-rotating twin-screw extruder, by optimizing the side feeding fiber adding process, the shearing effect of carbon fiber is reduced, and using carbon fiber filament as raw material, the carbon fiber can be made to retain a longer fiber length, which can effectively improve the mechanical properties of composite materials. By adopting the side feeding fiber adding process, the shearing effect of the screw on the fiber can be effectively reduced, the length of the retained fiber is increased, and the mechanical properties of the material are improved. DETAILED DESCRIPTION

[0020] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1 The preparation method of modified carbon fiber comprises the following steps: The carbon fiber fabric was placed in a reactor, condensed and refluxed in acetone at 70°C for 24 h, then rinsed and soaked in deionized water for more than 5 times, and then dried in a blast oven at 80°C for 12 h to obtain the desized carbon fiber; The desized carbon fiber fabric was immersed in a 2 wt% Michaelis acid ethanol solution at 30°C for 3 h, then taken out, rinsed with water three to four times to remove insoluble impurities on the surface of the carbon fiber, and dried in a blast oven at 80°C for 12 h to obtain activated carbon fiber; A mixed system of 100 ml of anhydrous ethanol and deionized water in a mass ratio of 9:1 was placed in a magnetic stirring device for uniform mixing, a certain amount of silane coupling agent was measured and dripped into the above mixed system drop by drop to prepare a silane coupling agent solution with a mass fraction of 0.5%, and magnetic stirring was performed for 45 minutes to hydrolyze the silane; a certain amount of hydroxylated multi-walled carbon nanotubes was weighed and dispersed in the above silane hydrolyzate, and magnetic stirring was performed for 20 minutes to prepare a carbon nanotube suspension system with a mass fraction of 0.5%, the above activated carbon fiber was immersed in the carbon nanotube suspension system for 10 minutes and then taken out, and then placed in a blast oven at 80°C for 4 hours, and then ultrasonically cleaned with a 1:1 mixed solution of deionized water and ethanol, and then placed in a blast oven at 80°C for 4 hours to obtain carbon fiber grafted with silanized carbon nanotubes; Polyvinyl alcohol was dissolved in dichloromethane to prepare a polyvinyl alcohol-dichloromethane solution with a concentration of 0.5%. The carbon fiber grafted with silanized carbon nanotubes was immersed in the polyvinyl alcohol-dichloromethane solution for 20 minutes, drained, and dried in a forced air oven at 80° C. for 4 hours to obtain modified carbon fiber.

[0022] A method for preparing high-strength engineering plastics by using recycled PA66 plastics comprises the following steps: The recycled automobile water tanks containing PA66 plastic are unpacked, roughly sorted to remove large impurities, magnetic metals and non-magnetic metals, and then manually sorted, wet crushed, washed with hot alkaline water to remove oil stains, dried, electrostatically sorted, infrared and color finely sorted, and then put into the warehouse for homogenization; The homogenized automobile water tank crushed material was premixed with 1.8 parts by weight of epoxy resin, a chain extender of a diepoxy group, and 0.2 parts by weight of an antioxidant 1010, and then added to a co-rotating twin-screw extruder. After the first extrusion process, the chain-extended and viscosity-enhanced rPA66 was obtained by pelletizing. The rotation speed of the co-rotating twin-screw extruder was 400 rpm and the temperature was 260°C. 25 parts by weight of the above rPA66, 0.2 parts by weight of the hindered phenol 1098 antioxidant, 0.4 parts by weight of the lubricant CF-201, 5 parts by weight of the compatibilizer maleic anhydride grafted polyolefin elastomer, 0.1 parts by weight of black sand carbon black and 0.3 parts by weight of the hindered amine 944 light stabilizer are put into a high-speed mixer and mixed to obtain a premix; The remaining 25 parts by weight of rPA66 are fed into the main feeding port of the co-rotating twin-screw extruder using a loss-in-weight scale, the premix is ​​fed into the first side feeding port, and 28 parts by weight of modified carbon fiber are fed into the second feeding port, and a second extrusion process is performed to obtain a high-strength engineering plastic prepared using recycled PA66 plastic, wherein the rotation speed of the co-rotating twin-screw extruder is 400 rpm and the temperature is 260°C.

[0023] Example 2 The preparation method of modified carbon fiber comprises the following steps: The carbon fiber fabric was placed in a reactor, condensed and refluxed in acetone at 70°C for 24 h, then rinsed and soaked in deionized water for more than 5 times, and then dried in a blast oven at 80°C for 12 h to obtain the desized carbon fiber; The desized carbon fiber fabric was immersed in a 2 wt% Michaelis acid ethanol solution at 30°C for 3 h, then taken out, rinsed with water three to four times to remove insoluble impurities on the surface of the carbon fiber, and dried in a blast oven at 80°C for 12 h to obtain activated carbon fiber; A mixed system of 100 ml of anhydrous ethanol and deionized water in a mass ratio of 9:1 was placed in a magnetic stirring device for uniform mixing, a certain amount of silane coupling agent was measured and dripped into the above mixed system drop by drop to prepare a silane coupling agent solution with a mass fraction of 0.5%, and magnetic stirring was performed for 45 minutes to hydrolyze the silane; a certain amount of hydroxylated multi-walled carbon nanotubes was weighed and dispersed in the above silane hydrolyzate, and magnetic stirring was performed for 20 minutes to prepare a carbon nanotube suspension system with a mass fraction of 0.4%, the above activated carbon fiber was immersed in the carbon nanotube suspension system for 10 minutes and then taken out, and then placed in a blast oven at 80°C for 4 hours, and then ultrasonically cleaned with a 1:1 mixed solution of deionized water and ethanol, and then placed in a blast oven at 80°C for 4 hours to obtain carbon fiber grafted with silanized carbon nanotubes; Polyvinyl alcohol was dissolved in dichloromethane to prepare a polyvinyl alcohol-dichloromethane solution with a concentration of 0.3%. The carbon fiber grafted with silanized carbon nanotubes was immersed in the polyvinyl alcohol-dichloromethane solution for 20 minutes, drained, and dried in a forced air oven at 80° C. for 4 hours to obtain modified carbon fiber.

[0024] The components and method for preparing high-strength engineering plastics using recycled PA66 plastics are the same as those in Example 1.

[0025] Example 3 The preparation method of modified carbon fiber comprises the following steps: The carbon fiber fabric was placed in a reactor, condensed and refluxed in acetone at 70°C for 24 h, then rinsed and soaked in deionized water for more than 5 times, and then dried in a blast oven at 80°C for 12 h to obtain the desized carbon fiber; The desized carbon fiber fabric was immersed in a 2 wt% Michaelis acid ethanol solution at 30°C for 3 h, then taken out, rinsed with water three to four times to remove insoluble impurities on the surface of the carbon fiber, and dried in a blast oven at 80°C for 12 h to obtain activated carbon fiber; A mixed system of 100 ml of anhydrous ethanol and deionized water in a mass ratio of 9:1 was placed in a magnetic stirring device for uniform mixing, a certain amount of silane coupling agent was measured and dripped into the above mixed system drop by drop to prepare a silane coupling agent solution with a mass fraction of 0.5%, and magnetic stirring was performed for 45 minutes to hydrolyze the silane; a certain amount of hydroxylated multi-walled carbon nanotubes was weighed and dispersed in the above silane hydrolyzate, and magnetic stirring was performed for 20 minutes to prepare a carbon nanotube suspension system with a mass fraction of 0.5%, the above activated carbon fiber was immersed in the carbon nanotube suspension system for 10 minutes and then taken out, and then placed in a blast oven at 80°C for 4 hours, and then ultrasonically cleaned with a 1:1 mixed solution of deionized water and ethanol, and then placed in a blast oven at 80°C for 4 hours to obtain carbon fiber grafted with silanized carbon nanotubes; Polyvinyl alcohol was dissolved in acetone to prepare a polyvinyl alcohol-acetone solution with a concentration of 0.3%. The carbon fiber grafted with silanized carbon nanotubes was immersed in the polyvinyl alcohol-dichloromethane solution for 20 minutes, drained, and dried in a forced air oven at 80°C for 4 hours to obtain the carbon fiber.

[0026] A method for preparing high-strength engineering plastics by using recycled PA66 plastics comprises the following steps.

[0027] Example 4 A method for preparing high-strength engineering plastics by using recycled PA66 plastics comprises the following steps: The recycled automobile water tanks containing PA66 plastic are unpacked, roughly sorted to remove large impurities, magnetic metals and non-magnetic metals, and then manually sorted, wet crushed, washed with hot alkaline water to remove oil stains, dried, electrostatically sorted, infrared and color finely sorted, and then put into the warehouse for homogenization; The homogenized automobile water tank crushed material was premixed with 1.8 parts by weight of epoxy resin, a chain extender of a diepoxy group, and 0.2 parts by weight of an antioxidant 1010, and then added to a co-rotating twin-screw extruder. After the first extrusion process, the chain-extended and viscosity-enhanced rPA66 was obtained by pelletizing. The rotation speed of the co-rotating twin-screw extruder was 400 rpm and the temperature was 260°C. 20 parts by weight of the above rPA66, 0.2 parts by weight of the hindered phenol 1098 antioxidant, 0.4 parts by weight of the lubricant CF-201, 6 parts by weight of the compatibilizer maleic anhydride grafted polyolefin elastomer, 0.1 parts by weight of black sand carbon black and 0.4 parts by weight of the hindered amine 944 light stabilizer are put into a high-speed mixer and mixed to obtain a premix; The remaining 25 parts by weight of rPA66 are fed into the main feeding port of the co-rotating twin-screw extruder using a loss-in-weight scale, the premix is ​​fed into the first side feeding port, and 29 parts by weight of modified carbon fiber are fed into the second feeding port, and a second extrusion process is performed to obtain a high-strength engineering plastic prepared using recycled PA66 plastic, wherein the rotation speed of the co-rotating twin-screw extruder is 400 rpm and the temperature is 260°C.

[0028] The components and preparation method of the modified carbon fiber are the same as those in Example 1.

[0029] Comparative Example 1 The preparation method of modified carbon fiber comprises the following steps: The desizing step is the same as that in Example 1, to obtain desizing carbon fiber; The activation step is the same as that in Example 1 to obtain activated carbon fibers; A mixed system of 100 ml of anhydrous ethanol and deionized water in a mass ratio of 9:1 was placed in a magnetic stirring device for uniform mixing, a certain amount of silane coupling agent was measured and dripped into the above mixed system drop by drop to prepare a silane coupling agent solution with a mass fraction of 0.5%, and the silane was hydrolyzed by magnetic stirring for 45 minutes; a certain amount of hydroxylated multi-walled carbon nanotubes was weighed and dispersed in the above silane hydrolyzate, and magnetic stirring was performed for 20 minutes to prepare a carbon nanotube suspension system with a mass fraction of 0.5%, the above activated carbon fiber was immersed in the carbon nanotube suspension system for 10 minutes and then taken out, and then placed in a blast oven to dry at 80°C for 4 hours, and then ultrasonically cleaned with a 1:1 mixed solution of deionized water and ethanol, and then placed in a blast oven to dry at 80°C for 4 hours to obtain carbon fiber grafted with silanized carbon nanotubes, which is a modified carbon fiber.

[0030] The components and method for preparing high-strength engineering plastics using recycled PA66 plastics are the same as those in Example 1.

[0031] Comparative Example 2 The preparation method of modified carbon fiber comprises the following steps: The desizing step is the same as that in Example 1, to obtain desizing carbon fiber; The activation step is the same as that in Example 1 to obtain activated carbon fibers; Polyvinyl alcohol was dissolved in dichloromethane to prepare a polyvinyl alcohol-dichloromethane solution with a concentration of 0.5%. The activated carbon fiber was immersed in the polyvinyl alcohol-dichloromethane solution for 20 minutes, drained, and dried in a blast oven at 80°C for 4 hours to obtain a carbon fiber covered with a thin layer of polyvinyl alcohol, which is a modified carbon fiber.

[0032] The components and method for preparing high-strength engineering plastics using recycled PA66 plastics are the same as those in Example 1.

[0033] Comparative Example 3 The step of preparing modified carbon fibers is omitted.

[0034] A method for preparing high-strength engineering plastics by using recycled PA66 plastics comprises the following steps: The recycled automobile water tanks containing PA66 plastic are unpacked, roughly sorted to remove large impurities, magnetic metals and non-magnetic metals, and then manually sorted, wet crushed, washed with hot alkaline water to remove oil stains, dried, electrostatically sorted, infrared and color finely sorted, and then put into the warehouse for homogenization; The homogenized automobile water tank crushed material was premixed with 1.8 parts by weight of epoxy resin, a chain extender of a diepoxy group, and 0.2 parts by weight of an antioxidant 1010, and then added to a co-rotating twin-screw extruder. After the first extrusion process, the chain-extended and viscosity-enhanced rPA66 was obtained by pelletizing. The rotation speed of the co-rotating twin-screw extruder was 400 rpm and the temperature was 260°C. 25 parts by weight of the above rPA66, 0.2 parts by weight of the hindered phenol 1098 antioxidant, 0.4 parts by weight of the lubricant CF-201, 5 parts by weight of the compatibilizer maleic anhydride grafted polyolefin elastomer, 0.1 parts by weight of black sand carbon black and 0.3 parts by weight of the hindered amine 944 light stabilizer are put into a high-speed mixer and mixed to obtain a premix; The remaining 25 parts by weight of rPA66 are fed into the main feeding port of the co-rotating twin-screw extruder using a loss-in-weight scale, the premix is ​​fed into the first side feeding port, and 28 parts by weight of carbon fiber are fed into the second feeding port, and a second extrusion process is performed to obtain a high-strength engineering plastic prepared using recycled PA66 plastic, wherein the rotation speed of the co-rotating twin-screw extruder is 400 rpm and the temperature is 260°C.

[0035] Comparative Example 4 A method for preparing high-strength engineering plastics by using recycled PA66 plastics comprises the following steps: The recycled automobile water tanks containing PA66 plastic are unpacked, roughly sorted to remove large impurities, magnetic metals and non-magnetic metals, and then manually sorted, wet crushed, washed with hot alkaline water to remove oil stains, dried, electrostatically sorted, infrared and color finely sorted, and then put into the warehouse for homogenization; The homogenized automobile water tank crushed material was premixed with 1.8 parts by weight of epoxy resin, a chain extender of a diepoxy group, and 0.2 parts by weight of an antioxidant 1010, and then added to a co-rotating twin-screw extruder. After the first extrusion process, the chain-extended and viscosity-enhanced rPA66 was obtained by pelletizing. The rotation speed of the co-rotating twin-screw extruder was 400 rpm and the temperature was 260°C. 20 parts by weight of the above rPA66, 0.2 parts by weight of the hindered phenol 1098 antioxidant, 0.4 parts by weight of the lubricant CF-201, 6 parts by weight of the compatibilizer maleic anhydride grafted polyolefin elastomer, 0.1 parts by weight of black sand carbon black and 0.4 parts by weight of the hindered amine 944 light stabilizer are put into a high-speed mixer and mixed to obtain a premix; The remaining 25 parts by weight of rPA66, the premix and 29 parts by weight of modified carbon fiber are added to a co-rotating twin-screw extruder for a second extrusion process to obtain high-strength engineering plastics prepared using recycled PA66 plastic, wherein the rotation speed of the co-rotating twin-screw extruder is 400 rpm and the temperature is 260°C.

[0036] The components and preparation method of the modified carbon fiber are the same as those in Example 1.

[0037] Performance Testing Tensile performance test: According to GB / T 1040-2006, a universal testing machine was used to apply a load of 50 N to the sample, and the crosshead speed was set to 5 mm / min to test the tensile strength, tensile modulus and elongation at break of PA66 / CF composite materials. Each group of samples was repeated 5 times, and the results were averaged; the tensile strength was ≥110MPa and qualified. The test results are shown in the following table: Bending performance test: According to GB / T 9341-2008, the load is set to 5 N, and the bending strength and bending modulus of PA66 / CF composite materials are tested. Five control groups are set for each group of samples, and the results are averaged. The test results are shown in the following table: Izod notched impact strength test: According to GB / T 1843-2008, the pendulum is set to 2.75 J to test the impact strength of PA66 / CF composite materials. Each group of samples is repeated 5 times and the results are averaged. The test results are shown in Table 1: Table 1: Statistical table of mechanical properties test data of Examples 1-4 and Comparative Examples 1-4 As can be seen from the above table, the high-strength engineering plastics prepared from recycled PA66 plastics in Examples 1-4 of the present invention have large tensile strength, flexural strength and impact strength, excellent mechanical properties, and can meet the testing requirements of the office chair industry. In Comparative Example 1, the step of soaking in polyvinyl alcohol-dichloromethane solution is omitted, that is, no polyvinyl alcohol thin layer is formed on the carbon fiber grafted with silanized carbon nanotubes, and in Comparative Example 2, the carbon nanotube suspension system is not soaked, that is, no silanized carbon nanotubes are grafted on the carbon fiber. In Comparative Example 3, the carbon fiber is not treated in any way, and the PA66 is directly reinforced with the carbon fiber. In Comparative Example 4, in the second extrusion process, the main / side feeding processing method is not distinguished, and the measured tensile strength, bending strength and impact strength are significantly reduced, and the reduction is obvious in Comparative Example 3, indicating that the modification of carbon fiber by grafting silanized carbon nanotubes and forming a polyvinyl alcohol film can have an excellent reinforcement effect on PA66 and improve the mechanical properties of the obtained high-strength engineering plastics. The reinforcement effect of carbon fiber on PA66 can also be improved by optimizing the side feeding fiber adding process.

[0038] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing high-strength engineering plastics by recycling PA66 plastics, characterized in that: At least the following steps are included: The recycled PA66 plastic is put into the warehouse for homogenization; The homogenized PA66 plastic is crushed, premixed evenly with the chain extender and the first antioxidant, and subjected to a first extrusion process to obtain rPA66; Put part of the rPA66, the second antioxidant, the lubricant, the compatibilizer, the black sand and the light stabilizer into a high-speed mixer and mix them to obtain a premix; The premix, the modified carbon fiber and the remaining rPA66 are subjected to a second extrusion process to obtain a high-strength engineering plastic prepared by using recycled PA66 plastic; Wherein, the modified carbon fiber is obtained by modification with silane coupling agent, carbon nanotubes and polyvinyl alcohol.

2. The method for preparing high-strength engineering plastics by recycling PA66 plastics according to claim 1, characterized in that: The prepared high-strength engineering plastics include at least the following raw materials in parts by weight: rPA66 45.0-50.0; Modified carbon fiber 22.0-29.0; Grafting extender 3.5-6.0; Lubricant 0.2-0.4; Second antioxidant 0.1-0.2; Black sand 0.08-0.1; Light stabilizer 0.2-0.

4.

3. The method for preparing high-strength engineering plastics by recycling PA66 plastics according to claim 1, characterized in that: The method for preparing the modified carbon fiber comprises at least the following steps: The carbon fiber is condensed and refluxed in acetone at 60-80°C for 20-26 hours, rinsed and soaked with deionized water, and dried in a blast oven at 80-90°C for 10-15 hours to obtain desizing carbon fiber; The desized carbon fiber is immersed in a 1-3 wt % Michaelis acid ethanol solution at 20-30° C. for 2-4 hours, then rinsed to remove insoluble impurities on the surface, and dried in a blast oven at 80-90° C. for 10-15 hours to obtain an activated carbon fiber; Dispersing carbon nanotubes in a silane coupling agent solution, magnetically stirring for 20-40 minutes, preparing a carbon nanotube suspension system with a mass fraction of 0.4-0.6%, soaking the activated carbon fiber in the carbon nanotube suspension system for 5-20 minutes, taking it out, and then putting it in a blast oven at 80-90° C. to dry for 3-5 hours, using a 1:1 mixed solution of deionized water and ethanol for ultrasonic cleaning, and after cleaning, putting it in a blast oven at 80-90° C. to dry for 3-5 hours to obtain carbon fiber grafted with silanized carbon nanotubes; Polyvinyl alcohol is dissolved in dichloromethane to prepare a polyvinyl alcohol-dichloromethane solution with a concentration of 0.3-0.6%, and the carbon fiber grafted with silanized carbon nanotubes is immersed in the polyvinyl alcohol-dichloromethane solution for 5-30 minutes, drained, and dried in a forced air oven at 80-90° C. for 3-5 hours to obtain the modified carbon fiber.

4. The method for preparing high-strength engineering plastics by recycling PA66 plastics according to claim 1, characterized in that: The first extrusion process and the second extrusion process are both carried out in a co-rotating twin-screw extruder, the premix is ​​fed into the first side feeding port of the co-rotating twin-screw extruder, the modified carbon fiber is fed into the second side feeding port of the co-rotating twin-screw extruder, and the remaining rPA66 is fed into the main feeding port of the co-rotating twin-screw extruder.

5. The method for preparing high-strength engineering plastics by using recycled PA66 plastics according to claim 1, characterized in that: The chain extender is a diepoxy group chain extender epoxy resin, and the first antioxidant is antioxidant 1010.

6. The method for preparing high-strength engineering plastics by recycling PA66 plastics according to claim 1, characterized in that: The second antioxidant is any one or more of a hindered phenol antioxidant or a phosphite antioxidant, the lubricant is CF-201, the compatibilizer is a maleic anhydride grafted polyolefin elastomer or a maleic anhydride grafted epoxy resin, the black sand is carbon black or a coupling agent, the light stabilizer is any one or more of a hindered phenol stabilizer, a phosphite stabilizer, a cuprous halide composite stabilizer or a stabilizer containing a dibenzene functional group compound, the carbon fiber is a carbon fiber filament, and the size of the carbon fiber filament is 5-15 mm.

7. The method for preparing high-strength engineering plastics by using recycled PA66 plastics according to claim 4, characterized in that: The rotation speed of the first extrusion process is 300-500 rpm and the temperature is 240-270°C.

8. The method for preparing high-strength engineering plastics by using recycled PA66 plastics according to claim 4, characterized in that: The rotation speed of the second extrusion process is 300-500 rpm and the temperature is 240-270°C.

9. The method for preparing high-strength engineering plastics by using recycled PA66 plastics according to claim 1, characterized in that: Before the recycled PA66 plastic is put into storage for homogenization, it is at least unpacked, roughly sorted to remove large impurities, remove magnetic metals and non-magnetic metals, manually sorted, wet crushed, washed with hot alkaline water to remove oil stains, dried, electrostatically sorted, and infrared and color fine sorted.

10. Application of high-strength engineering plastics obtained by the method for preparing high-strength engineering plastics by recycling PA66 plastics as described in any one of claims 1 to 9 in office chairs, gaming chairs, home appliances, automobiles or power tool industries.

Citation Information

Patent Citations

  • Carbon nanotube modified carbon fiber composite for automobile hubs and preparation method of composite

    CN106905695A

  • Special high-strength composite material adopting recycled nylon for automobile structural part

    CN112457557A

  • Preparation method of nano-cellulose / carbon nanotube / polyvinyl alcohol synergistically modified carbon fiber

    CN113463376A

  • Molded article of polyacetal resin

    JP2009286961A